Tinjauan Hukum Tentang Kebebasan Berpendapat dari Aspek Hukum Positif dan Hukum Islam (Studi Kasus Bima Lampung) - Sutan Bakti Harahap; Rahmat Hidayat (UNES Law Review, 2023)
This research aims to examine the regulation of the rights of freedom of speech in the realm of positive law and Islamic law, and to look at its application on social media platforms. The main focus of this research is on the case of Bima's action, is it a violation of the law? This qualitative research uses a juridical-emperical approach, in which case analysis is based on various existing sources. This research refers to two main perspectives, namely Positive Law and Islamic Law. The findings of this research show that a negative image is reflected in the Lampung Provincial Government. This is because the majority of people think that the Lampung Provincial Government limits freedom of speech and criticism. It is also known that the criticism delivered by Bima did not fulfil the elements and conditions so that it could not be criminalised. In line with positive law, based on Al Maududi's view, Islam does not prohibit expressing opinions at all. However, it should be noted that in expressing opinions, certain limits must be observed, especially in terms of the use of polite language. No less important is also the ITE Law which is still a polemic until now, because of the discrepancy between expectations and facts in the field. So, it is necessary for further explanation.